Pembagian Harta Waris Pada Adat Waris Tunggu Tubang Dalam Perspektif Kompilasi Hukum Islam - Ahmad Hadzikil Fahimi (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The Tubang inheritance tradition uses a female major inheritance system. The customary inheritance of the Tunggu Tubang heirs differs from the heirs listed in the Compilation of Islamic Law and the portion that all heirs receive in the customary inheritance of the Tunggu Tubang with the Compilation of Islamic Law. The Compilation of Islamic Law is the rules modified in such a way as to adapt to the customs and culture that occur in Indonesia. One of the sections contained in the Compilation of Islamic Law is the division of inheritance. The results of this study provide a law that in the division of the customary inheritance of Tunggu Tubang is not included as inheritance, because the articles in the Compilation of Islamic Law have many differences, but the customary inheritance of Tunggu Tubang can be said to be a gift. The customary inheritance of the Tunggu Tubang can be called a grant because the giving of grants to heirs is referred to as an inheritance. The inheritance tradition of the Tunggu Tubang which gives their wealth to the eldest daughter who is included in the heirs is sufficient if it is called a grant and also the inheritance that has been given to Tunggu Tubang can be withdrawn by the parents if it is not used as well as possible.